2022
DOI: 10.1155/2022/3807013
|View full text |Cite
|
Sign up to set email alerts
|

Steep End-Slope Mining and Slope Stability of Extremely Thick Inclined Coal Seam Open-Pit Mine

Abstract: Considering the characteristics of extremely thick inclined open-pit coal mine with large amount under end slope, large end-slope height, and long exposure time, it is important to study the slope stability research during open-pit mining. This study takes the whole process of excavation descending and steep end-slope mining of an extremely thick inclined open-pit mine as the background. The slope stability factor of the end slopes were calculated for each stage of mining with different coal seam thicknesses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, when the mining height of the equipment is increased, the prior experience of retaining twice the mining height is regarded to be conservative, and numerical simulation is recommended to determine it. Wang [36] suggested that the interlayer thickness should be greater than the height of the mining roof arch with a certain safety distance, generally above 3.0 m. Newman and Zipf [37] used a simple beam model to propose an equation for the thickness and tensile strength of the interlayer, which is calculated over 0.45 m for the entry width of 3.16 m.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the mining height of the equipment is increased, the prior experience of retaining twice the mining height is regarded to be conservative, and numerical simulation is recommended to determine it. Wang [36] suggested that the interlayer thickness should be greater than the height of the mining roof arch with a certain safety distance, generally above 3.0 m. Newman and Zipf [37] used a simple beam model to propose an equation for the thickness and tensile strength of the interlayer, which is calculated over 0.45 m for the entry width of 3.16 m.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of end slope mining : Wang et al analyzed the horizontal stress data of the slope and found that the horizontal stress follows a pattern of initially increasing and then decreasing during excavation and steep slope mining. [28] . Liu et al optimized the width of end slope mining road in open-pit mines, proposed an end slope mining scheme and carried out a simulation analysis method for slope stability [29] .…”
Section: Introductionmentioning
confidence: 99%
“…According to the eld investigation and Google Earth images, Hu et al [11] analyzed the process of fracture propagation on the slope under underground mining and then investigated the failure mechanism of the slope by the numerical software RFPA3D. Taking the process of excavation of the open-pit mine as the background, Wang et al [12] analyzed the slope stability factor of the end slopes using the strength reduction method, which shows that the vertical stress and stability factor decreased with the process of excavation, while the horizontal stress initially increased and then decreased. Wang et al [13] proposed a displacement-statistics-based discrete element method and then investigated the stability of the jointed rocky slopes by incorporating the shear strength reduction method into the proposed modeling method.…”
Section: Introductionmentioning
confidence: 99%